RANCANG BANGUN SOLAR TRACKER DUA AXIS MENGGUNAKAN PENGGERAK AIR - Muhammad ifdansyah; Sopian Arif; Ocsirendi Ocsirendi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Indonesia as a tropical country has the potential to develop and utilize solar energy as one of the many solar energy conversion systems, this solar energy conversion system can be applied to overcome the depletion of existing conventional fuel reserves. The main objective of this final project is to determine the effect of solar tracker angle on solar panel power on 1 axis and 2 axis solar tracker. The angle of the solar tracker affects the performance of the solar panel, namely the closer it is perpendicular to the arrival of the solar light, the greater the voltage and current. Solar cells that use a tracker are able to absorb solar energy more optimally than those without a tracker. The power absorbed by the 2 axis solar tracker is very large, so this tool has a greater power efficiency than previous technologies.